2017
DOI: 10.1016/j.jtho.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Computational Pathological Image Analysis Predicts Lung Cancer Prognosis

Abstract: Introduction Pathological examination of histopathological slides is a routine clinical procedure for lung cancer diagnosis and prognosis. Although the classification of lung cancer has been updated to become more specific, only a small subset of the total morphological features are taken into consideration. The vast majority of the detailed morphological features of tumor tissues, particularly tumor cells’ surrounding microenvironment, are not fully analyzed. The heterogeneity of tumor cells and close interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
136
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 37 publications
5
136
0
Order By: Relevance
“…Manual analysis involves assessments of features such as cellular morphology, nuclear structure, or tissue architecture, and such pre-specified image features have been inputted into support vector machines or random forests for tumor subtype classification and survival outcome analysis, e.g. (Luo et al 2017;Yu et al 2016;Mousavi et al 2015). However, pre-specified features may not generalize well across tumor types, so recent studies have focused on fully-automated approaches using convolutional neural networks (CNNs), bypassing the feature specification step.…”
Section: Introductionmentioning
confidence: 99%
“…Manual analysis involves assessments of features such as cellular morphology, nuclear structure, or tissue architecture, and such pre-specified image features have been inputted into support vector machines or random forests for tumor subtype classification and survival outcome analysis, e.g. (Luo et al 2017;Yu et al 2016;Mousavi et al 2015). However, pre-specified features may not generalize well across tumor types, so recent studies have focused on fully-automated approaches using convolutional neural networks (CNNs), bypassing the feature specification step.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor tissue slide scanning is becoming part of routine clinical practice for the acquisition of high resolution tumor histological details. In recent years, several computer algorithms for hematoxylin and eosin (H&E) stained pathology image analysis have been developed to aid pathologists in objective clinical diagnosis and prognosis [3][4][5][6][7] . Examples include an algorithm to extract stromal features 8 and an algorithm to assess cellular heterogeneity 6 as a prognostic factor in breast cancer.…”
mentioning
confidence: 99%
“…More recently, studies have shown that morphological features are associated with patient prognosis in lung cancer as well 4,5,7 . Deep learning methods, such as convolution neural networks (CNNs), have been widely used in image segmentation, object classification and recognition [9][10][11] and are now being adapted in biomedical image analysis to facilitate cancer diagnosis.…”
mentioning
confidence: 99%
“…Smoking is the leading risk factor for developing lung cancer, but not all of the smokers develop cancer, suggests that environmental and genetic factors contributes to the risk of cancer development [3]. Although new techniques are developed to detect lung cancer at an early stage, the prognosis is still poor [4]. Hence, development of new therapeutic strategies is still a need for achieving better survival rates.…”
Section: Introductionmentioning
confidence: 99%